Adaptabilty, stability and productivity of Eucalyptus grandis progenies - De Castro, Carlos Eduardo Caixeta [UNESP]; Da Silva, Paulo Henrique Muller; De Araújo, Marcio José [UNESP]; Miranda, Aline Cristina; De Moraes, Mario Luis Teixeira [UNESP]; De Paula, Rinaldo Cesar [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2018)
The forest breeding programs in Brazil aim at increasing productivity to meet the growing expected demand of wood. The objective of this study was to estimate genetic parameters and the stability of open-pollinated families of Eucalyptus grandis in different environments in Brazil, and also to propose selection strategies for the environments. 165 open-pollinated progenies were evaluated in eight environments in Monte Dourado- PA; Itamarandiba-MG; Anhembi, Capão Bonito, Lençóis Paulista and Pratânia-SP at age ranging between 36 and 51 months. The experimental design was randomized complete block design, planted in the spacing of 3.0 x 2.0 meters, with linear plots of 5 or 6 plants, and repetitions ranging from 4 to 8. Traits measured were: height, diameter at breast height and from these two traits volume was estimated. Results showed genotype-by-environment interaction, showing change in the ordering of Harmonic Mean of the Relative Performance of the Genetic Values (HMRPGV) method compared to the ordering by environments. Thus, simultaneous selection for all sites is not the best strategy. The sites of Pratânia and Monte Dourado B may be used for representative genotypes for most of the regions studied.
Adaptabilidade, estabilidade e produtividade de progênies de Eucalyptus grandis Hill ex Maiden
Keywords: Correlation; HMRPGV; Interaction; Tree breeding